Single Cell Mechanotype and Associated Molecular Changes in Urothelial Cell Transformation and Progression - Yu, Weibo; Lu, Qing-Yi; Sharma, Shivani; Ly, Chau; Di Carlo, Dino; Rowat, Amy C.; LeClaire, Michael; Kim, Donghyuk; Chow, Christine; Gimzewski, James K.; Rao, Jianyu (Frontiers in Cell and Developmental Biology, 2020)
Cancer cell mechanotype changes are newly recognized cancer phenotypic events, whereas metastatic cancer cells show decreased cell stiffness and increased deformability relative to normal cells. To further examine how cell mechanotype changes in early stages of cancer transformation and progression, an in vitro multi-step human urothelial cell carcinogenic model was used to measure cellular Young’s modulus, deformability, and transit time using single-cell atomic force microscopy, microfluidic-based deformability cytometry, and quantitative deformability cytometry, respectively. Measurable cell mechanotype changes of stiffness, deformability, and cell transit time occur early in the transformation process. As cells progress from normal, to preinvasive, to invasive cells, Young’s modulus of stiffness decreases and deformability increases gradually. These changes were confirmed in three-dimensional cultured microtumor masses and urine exfoliated cells directly from patients. Using gene screening and proteomics approaches, we found that the main molecular pathway implicated in cell mechanotype changes appears to be epithelial to mesenchymal transition.